IMPLEMENTASI BUDAYA KOREA PADA PERANCANGAN IDENTITAS VISUAL “MIREOKKI” - Brian Alvin Hananto (Universitas Trisakti, 2020)
AbstractThe Implementation of Korean Culture in Mireokki’s Visual Identity Design. Globalization made Indonesia exposed to other nation’s cultures. One of the mainstream cultures that are being exposed to Indonesian peoples is the popular culture of Korea. From foods, music, films, lifestyles and also design artifacts from Korea can be found here in Indonesia. One of Korean’s food that is widely favored in Indonesia is tteokbokkis, in which tteokbokki became the basis for food innovation development conducted by Stefani Octavia from the department of Food Technology, Universitas Pelita Harapan. On a collaborative work held by the Department of Food Technology and the Department of Visual Communication Design, there is a visual identity design made by Shella Subagia towards the product developed by Octavia, called “Mireokki”. Using qualitative design methods, Subagia succeeded in designing a logo, packaging, digital promotion media and brand activation which incorporates visuals from the Korean culture. This article contains the research and assessment that the author had done on the design works made by Subagia. The conclusion is that the form implementation of external contexts can be performed when the designer had the basic ability to create a design that is coherent and also united. AbstrakImplementasi Budaya Korea pada Perancangan Identitas Visual “Mireokki”. Globalisasi membuat kita semakin terekspos dengan budaya-budaya luar. Salah satu bentuk budaya populer yang tengah dikonsumsi masyarakat Indonesia adalah budaya Korea. Mulai dari makanan, musik, film, gaya hidup sampai artefak-artefak desain dari Korea banyak ditemukan di Indonesia. Salah satu makanan Korea yang tengah digemari di Indonesia adalah tteokbokki. Jenis makanan tersebut menjadi referensi dari pengembangan makanan dan inovasi yang dilakukan oleh Stefani Octavia dari program studi Teknologi Pangan Universitas Pelita Harapan. Pengembangan dilakukan dalam rangka kerjasama antara program studi Teknologi Pangan dan Desain Komunikasi Visual, melalui perancangan identitas visual oleh Shella Subagia terhadap produk inovasi Octavia yang bernama “Mireokki”. Dengan menggunakan metode perancangan kualitatif, Subagia berhasil menggagas perancangan logo, kemasan, media digital promosi dan juga brand activation yang mengimplementasikan karakter visual dari budaya Korea. Tulisan ini berisi penelitian dan penilaian kritis terhadap proses perancangan yang dilakukan oleh Subagia. Simpulan yang dihasilkan bahwa implementasi rupa dari konteks eksternal dapat dilakukan selama desainer memiliki kemampuan dasar untuk menggagas desain yang koheren dan menyatu.